Calling out the nameless: CocoRosie's Posthuman sound world. Issue 3 (27th September 2017) - Johnson, Jake
Abstract: "To engage with CocoRosie requires absolute suspension of disbelief, " writes The Guardian. This has as much to do with their music as their appearance, for sisterly duo CocoRosie have embraced what they call a "posthuman kind of style" rooted in the dissolution of gender. In an effort to imagine a world beyond human constructions of gender, CocoRosie creates a sound world that reflects this aesthetic of a genderless futurity. Following Donna Haraway's notion of the posthuman occupying a "post‐gender world" and Drew Daniel's contention that "all sound is queer, " supposing sound can sound gendered or de‐gendered centers the discussion of posthumanity around the production and reception of sound. This discussion of CocoRosie, then, offers music scholars a particularly apt discursive model for examining what a post‐gender (and thus posthuman) sound world sounds like. CocoRosie's strange music, I contend, carries a transformative impulse and in turn sounds the undoing of gender itself.